Exploring the Impact of Optimism and Innovativeness on Consumer Purchase Intentions: The Mediating Role of Perceived Usefulness and Ease of Use in Live Commerce - Wicaksono, Teguh; Syahrani, Syahrani; Ariani, Gusti Meinar Girda; Royanti, Farhana; Gina, Wardatul (Yayasan Sinergi Kawula Muda, 2025)
This study aims to investigate the impact of Optimism and Innovativeness on Purchase Intention through the mediating roles of Perceived Usefulness and Perceived Ease of Use in the context of live commerce. The research type is explanatory method using survey for identifying the existence of relationships and effects among variables. The population of the study consists of 667,489 residents of Banjarmasin City, and the sampling is conducted using purposive sampling with a minimum sample size of 138 respondents who have made online purchases through live commerce platforms. Data was collected using questionnaires and analyzed using Partial Least Squares (PLS-SEM) techniques. The results indicate that Optimism has a significant impact on Perceived Usefulness, Perceived Ease of Use, and Intention to Purchase. Additionally, Innovativeness also significantly affects Perceived Usefulness and Perceived Ease of Use but does not directly affect Purchase Intention. Furthermore, Perceived Usefulness and Perceived Ease of Use have been porven to mediate the relationship between Optimism and Intention to Purchase, as well as between Innovativeness and purchase intention significantly. This research contributes to the digital marketing field literature, specifically in understanding the factors that influence consumer purchase intention through live commerce platforms. The findings also provide practical implications for e-commerce companies to enhance platform design to be more user-friendly and optimize technology usefulness perceptions to boost consumer purchase intentions.